Strategi Guru IPS dalam Membentuk Karakter Sosial Siswa di MTS Darussalam Rejotangan Tulungagung - Syafa Nabila Azzahra; Binti Maunah (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2024)
Education is very important in life which is not only limited to knowledge but also character values. This researcher formulated the focus of the research as follows: (1) What is the role of social studies teachers in shaping social character in students at MTs Darussalam Rejotangan Tulungagung?, (2) What is the form of social studies teachers' efforts in shaping social character in students at MTs Darussalam Rejotangan Tulungagung?, (3) What is the implementation of social studies teachers in shaping social character in students at MTs Darussalam Rejotangan Tulungagung?, (4) What is the impact of social character education on students at MTs Darussalam Rejotangan Tulungagung?. This study uses qualitative research approaches and descriptive research. The results of the study are known, First, the role of a teacher in shaping the social character of students with several encouragements and motivations for character education. Second, the efforts of teachers as facilitators and mediators of students in forming character attitudes, one of which is to be a good role model. Third, the implementation of teachers as a form of success in instilling character education in schools. Fourth, the impact of social character education that has been carried out by teachers on students at school.